Investigation of friction and wear characteristics of palm biodiesel - Fazal, M.A.; Haseeb, A.S. Md. Abdul; Masjuki, Haji Hassan (Elsevier, 2013)
Use of biodiesel in automobile engine is creating tribology related new challenges. The present study aims to assess the friction and wear characteristics of palm biodiesel at different concentration level by using four-ball wear machine. The investigated fuels were biodiesel (B100), diesel (B0) and three different biodiesel blends such as B10 (10% biodiesel in diesel), B20, B50. Tests were conducted at 75 °C under a normal load of 40 kg for 1 h at four different speeds viz, 600, 900, 1200 and 1500 rpm. Worn surfaces of the balls were examined by SEM. Results showed that wear and friction decreased with the increase of biodiesel concentration. The wear of steel ball in B100 was appeared to be 20% lower than that in diesel (B0).